Experimental investigation of pressure-drop characteristics across multi-layer porous metal structures - Oun, Hatem; Kennedy, Andrew R. (Springer Verlag, 2014)
This study investigates the effect of airflow (in the range of 0–70 m s-1) on the pressure-drop characteristics for a novel multi-layered, nickel-based porous metal, as a function of thickness (affected by sectioning) and density (affected by compression). In addition to generating unique data for these materials, the study highlights the need for precise pinpointing of the different flow regimes (Darcy, Forchheimer and Turbulent) in order to enable accurate determination of the permeability (K) and form drag coefficient (C) defined by the Forchheimer equation and to understand the complex dependence of length-normalised pressure drop on sample thickness.